Age-Related Olfactory Dysfunction: Epidemiology, Pathophysiology, and Clinical Management - Kondo, Kenji; Kikuta, Shu; Ueha, Rumi; Suzukawa, Keigo; Yamasoba, Tatsuya (Frontiers in Aging Neuroscience, 2020)
As other sensory systems, olfactory function deteriorates with age. Epidemiological studies have revealed that the incidence of olfactory dysfunction increases at the age of 60 and older and males are more affected than females. Moreover, smoking, heavy alcohol use, sinonasal diseases, and Down’s syndrome are associated with an increased incidence of olfactory dysfunction. Although the pathophysiology of olfactory dysfunction in humans remains largely unknown, studies in laboratory animals have demonstrated that both the peripheral and central olfactory nervous systems are affected by aging. Aged olfactory neuroepithelium in the nasal cavity shows loss of mature olfactory neurons, replacement of olfactory neuroepithelium by respiratory epithelium, and a decrease in basal cell proliferation both in the normal state and after injury. In the central olfactory pathway, a decrease in the turnover of interneurons in the olfactory bulb and reduced activity in the olfactory cortex under olfactory stimulation are observed. Recently, the association between olfactory impairment and neurodegenerative diseases, such as Alzheimer’s disease and Parkinson’s disease, has gained attention. Evidence-based pharmacotherapy to suppress or improve age-related olfactory dysfunction has not yet been established, but preliminary results suggest that olfactory training using odorants may be useful to improve some aspects of age-related olfactory impairment.